2005
DOI: 10.1002/hbm.20164
|View full text |Cite
|
Sign up to set email alerts
|

Human brain activation during passive listening to sounds from different locations: An fMRI and MEG study

Abstract: Recent animal and human studies indicate the existence of a neural pathway for sound localization, which is similar to the "where" pathway of the visual system and distinct from the sound identification pathway. This study sought to highlight this pathway using a passive listening protocol. We employed fMRI to study cortical areas, activated during the processing of sounds coming from different locations, and MEG to disclose the temporal dynamics of these areas. In addition, the hypothesis of different activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
68
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 31 publications
11
68
2
Order By: Relevance
“…Although lesions that include auditory cortex can impair sound localization in both animals and humans (Sanchez-Longo and Forster, 1958;Jenkins and Masterton, 1982;Thompson and Cortez, 1983;Hefner and Heffner, 1986;Zatorre and Penhune, 2001;Smith et al, 2004;King et al, 2007), human neuroimaging studies have had mixed success at identifying differential patterns of activation as a function of sound location. For monaural sounds, activation is stronger in the contralateral than in the ipsilateral primary auditory cortex (Woldorff et al, 1999;Petkov et al, 2004;Krumbholz et al, 2005a), but no contralateral preference has been found for more realistic binaural stimuli (Woldorff et al, 1999;Brunetti et al, 2005;Krumbholz et al, 2005b;Zimmer and Macaluso, 2005;Zimmer et al, 2006). Similar mixed results have occurred for other metrics of spatial sensitivity: one study found that, when stimuli were presented from a larger range of space, the area of activation in primary auditory cortex was larger (Brunetti et al, 2005), and one study using a similar strategy did not (Zatorre et al, 2002).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although lesions that include auditory cortex can impair sound localization in both animals and humans (Sanchez-Longo and Forster, 1958;Jenkins and Masterton, 1982;Thompson and Cortez, 1983;Hefner and Heffner, 1986;Zatorre and Penhune, 2001;Smith et al, 2004;King et al, 2007), human neuroimaging studies have had mixed success at identifying differential patterns of activation as a function of sound location. For monaural sounds, activation is stronger in the contralateral than in the ipsilateral primary auditory cortex (Woldorff et al, 1999;Petkov et al, 2004;Krumbholz et al, 2005a), but no contralateral preference has been found for more realistic binaural stimuli (Woldorff et al, 1999;Brunetti et al, 2005;Krumbholz et al, 2005b;Zimmer and Macaluso, 2005;Zimmer et al, 2006). Similar mixed results have occurred for other metrics of spatial sensitivity: one study found that, when stimuli were presented from a larger range of space, the area of activation in primary auditory cortex was larger (Brunetti et al, 2005), and one study using a similar strategy did not (Zatorre et al, 2002).…”
Section: Introductionmentioning
confidence: 91%
“…For monaural sounds, activation is stronger in the contralateral than in the ipsilateral primary auditory cortex (Woldorff et al, 1999;Petkov et al, 2004;Krumbholz et al, 2005a), but no contralateral preference has been found for more realistic binaural stimuli (Woldorff et al, 1999;Brunetti et al, 2005;Krumbholz et al, 2005b;Zimmer and Macaluso, 2005;Zimmer et al, 2006). Similar mixed results have occurred for other metrics of spatial sensitivity: one study found that, when stimuli were presented from a larger range of space, the area of activation in primary auditory cortex was larger (Brunetti et al, 2005), and one study using a similar strategy did not (Zatorre et al, 2002).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Only relatively broad anatomical divisions, such as that between the anterior "what" vs. posterior "where" (8)(9)(10)(11)(12)(13) pathways, have been shown in human neuroimaging studies. The posterior auditory "where" pathway, which encompasses nonprimary auditory cortex areas including the planum temporale (PT) and posterior superior temporal gyrus (STG), is strongly activated by horizontal sound direction changes (12,(14)(15)(16) and movement (17,18). However, although human (19,20) (and nonhuman primate, refs.…”
mentioning
confidence: 99%
“…EEG studies using source-localization also identified the pSTG-Spt region of the ADS as the sound localization processing center ( Tata & Ward, 2005a; Tata & Ward, 2005b). A combined fMRI and MEG study corroborated the role of the ADS with audiospatial processing by demonstrating that changes in sound location resulted in activation spreading from Heschl’s gyrus posteriorly along the pSTG and terminating in the IPL ( Brunetti et al , 2005). In another MEG study, the IPL and frontal lobe were shown active during maintenance of sound locations in working memory ( Lutzenberger et al , 2002).…”
Section: Introductionmentioning
confidence: 83%